2014
DOI: 10.1088/0026-1394/51/5/552
|View full text |Cite
|
Sign up to set email alerts
|

New standards of absorbed dose to water under reference conditions by graphite calorimetry for60Co and high-energy x-rays at LNE-LNHB

Abstract: The LNE-LNHB has developed two primary standards to determine the absorbed dose to water under reference conditions (for 10 cm × 10 cm) in 60 Co, 6 MV, 12 MV and 20 MV photon beams: a new graphite calorimeter and a water calorimeter. This first paper presents the results obtained with the graphite calorimeter and the new associated methodology. The associated relative standard uncertainty (k = 1) of absorbed dose to water is 0.25% for 60 Co and lies between 0.32% to 0.35% for MV x-ray beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(84 reference statements)
1
4
1
Order By: Relevance
“…It should be mentioned, for clarification, that the ratios k Q 3x3 /k Q 10x10 would be even larger if the correction factors k v from table 3 had not been applied. To some extent, the finding of an increasing ratio k Q 3x3 /k Q 10x10 is in contrast to other published data (Krauss et al 2011, Delaunay et al 2011, Delaunay et al 2012 which showed no significant variation of the k Q factors with beam size. However, these measurements have not been performed for photon beams with generating voltage higher than 12 MV and from figure 7 it is evident that the conclusion of a linear increase is mainly affected just by the k Q 3x3 /k Q 10x10 value at 25 MV.…”
Section: K Q Factors and Ratios Kcontrasting
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned, for clarification, that the ratios k Q 3x3 /k Q 10x10 would be even larger if the correction factors k v from table 3 had not been applied. To some extent, the finding of an increasing ratio k Q 3x3 /k Q 10x10 is in contrast to other published data (Krauss et al 2011, Delaunay et al 2011, Delaunay et al 2012 which showed no significant variation of the k Q factors with beam size. However, these measurements have not been performed for photon beams with generating voltage higher than 12 MV and from figure 7 it is evident that the conclusion of a linear increase is mainly affected just by the k Q 3x3 /k Q 10x10 value at 25 MV.…”
Section: K Q Factors and Ratios Kcontrasting
confidence: 99%
“…the ratio of k Q factors in the 3 cm × 3 cm and in the reference field (10 cm × 10 cm), was close to one within the standard uncertainty of about 0.4%. A similar result was achieved at Laboratoire National Henri Bequerel (LNE-LNHB), where k Q factors by means of graphite calorimetry were determined in 4 cm × 4 cm and 2 cm × 2 cm beams of 6 MV and 12 MV photons (Delaunay et al 2011). They concluded that the measured k Q values for NE 2577 and Exradin A1SL chambers showed no variation with the beam size within the experimental standard uncertainies.…”
Section: Introductionsupporting
confidence: 72%
“…In small beams (2 cm × 2 cm) the thermal feedback between the core and the jacket has proven its interest when the jacket is not uniformly irradiated, leading to a relative uncertainty on the mean absorbed dose to core of about 0.18%. The results of the measurements with the GR-10 graphite calorimeter in the 2 cm × 2 cm size in the frame of the JRP7 project have been reported during this symposium [12] and will be the subject of another publication.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the vials were placed one by one in a 30 × 30 × 30 cm 3 water tank, their geometrical center at 10 cm depth and their longitudinal axis perpendicular to the beam axis (figure 1(a)). The absorbed dose to water values are directly traceable to the French national references based on calorimetry primary measurements [33].…”
Section: Specific Irradiation and Reading Conditions For The Studiesmentioning
confidence: 99%